Technical assistance on agriculture : IICA CIDA project number 540/13127: inception report - Agence Canadienne pour le Developpement International (ACDI) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
This report includes the purpose of the project a summary, first-year review and adjustment, budget resume, project plans, issues and adjustment by IICA program area, including: activity description, progress and adjustment, implementation shedule, budget overview, statement of objectives, expected results and indicators for the evaluation plan. It also presents project management and coordination structure, and an evalation plan. Two annexes are included: activity worksheets and revised detailed budget by project activity.